Phenotypic Characterization of Intellectual Disability Caused by MBOAT7 Mutation in Two Consanguineous Pakistani Families - Sun, Liwei; Khan, Amjad; Zhang, Han; Han, Shirui; Habulieti, Xiaerbati; Wang, Rongrong; Zhang, Xue (Frontiers in Pediatrics, 2020)
A homozygous in-frame deletion (c. 758_778del; p. Glu253_Ala259del) in MBOAT7 gene, which also known as lysophosphatidylinositol acyltransferase (LPIAT1), was reported to be the genetic cause for intellectual disability (ID) in consanguineous families from Pakistan previously. Here we identified two more Pakistani consanguineous families with severe ID individuals sharing the same homozygous variant. Thus, we provide more evidence for indicating it as a founder variant and a mutational hot spot. In order to further elucidate the genotype-phenotype relationships of the in-frame deletion in MBOAT7 gene, which is poorly studied at present, we located the variant in the transmembrane domain, and conducted molecular analysis of the protein to characterize that the alteration of the variant in three-dimensional positioning causes steric hinderance to the formation of α-helix and hydrogen bond, which may influence its effectiveness as a functional transmembrane protein. Moreover, extensive neuropsychological observations, clinical interviews and genetic analysis were performed on 6 patients from the 2 families, and unique features such as severe paraplegia, feeding refusal, and self-injurious behavior were reported for the first time, which expand the current knowledge regarding the phenotypic spectrum of severe ID caused by MBOAT7，and it is crucial for optimal management for symptoms alleviation and appropriate screening in these patients.